Field notes contributed by Robert K. Myers, fall 1988 - Myers, Robert K.et al (1988)
List of birds and locations contributed by Robert K. Myers This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of fall 1988. Epson - sheet feed